เฮลิโคแบคเตอร์ ไพโลไร รูปร่างทรงกลม ซึ่งมีชีวิต แต่ไม่เจริญเติบโต ยังคงสร้างกลูตามิลทรานส์เพปทิเดสที่เป็นปัจจัยก่อความรุนแรงโรค - มณีธร, เพชรี; โรจน์พิบูลสถิตย์, ปนัดดา; วิไลชนม์, รัฐกร; กังสดาลอำไพ, ศศิชัย (Thai Journal of Science and Technology, 2018)
Abstract Helicobacter pylori usually presents in a spiral-shape, but in a stress condition, it adapts to a coccoid form which is viable but non-culturable (VBNC). Previous studies reported that the VBNC coccoids still produce mRNAs of some virulence factors. g-Glutamyl transpeptidase (GGT) is an enzyme involving in the bacterial colonization and has not been studied in the coccoid form of the bacteria. This study aims to investigate the expression of ggt gene of the coccoids. The spiral H. pylori required low level of oxygen was transformed into the coccoid form by an exposure to the ambient oxygen for a period of time and the transcriptional level of the coccoid ggt gene was compared to that of the spiral bacteria. After 9 hours of the oxygen exposure, it was observed that the spiral-shape bacteria changed into the full coccoids and continuously expressed ggt mRNA. It revealed that even in the VBNC coccoid form, the H. pylori still produce its virulence factor that is important for the bacterial colonization. This situation can occur when the bacteria are accidentally contaminated to the environment and, therefore, the bacterial infection would be critically uncontrollable. Keywords: Helicobacter pylori; gamma-glutamyl transpeptidase; coccoid